Numerical analysis of non-aligned inputs M-type micromixers with different shaped obstacles for biomedical applications. (June 2022) - Irfan, Muhammad; Shah, Imran; Niazi, Usama M; Ali, Muhsin; Ali, Sadaqat; Jalalah, Mohammed S; Asif Khan, Muhammad K; Almawgani, Abdulkarem Hussein Mohammed; Rahman, Saifur
Fluid mixing in lab-on-a-chip devices at laminar flow conditions result in a low mixing index. The reason is dominant diffusion over the convection process. The mixing index can be improved by certain changes in the micromixer structural design like introducing obstacles in the path of fluid flow. These obstacles will make dominant the advection process over the diffusion process. The main contribution of this work is based on proposing the novel hybrid type micromixer design for enhancing the mixing quality. Three non-aligned M-type and non-aligned M-type with obstacles passive type micromixers are analyzed by COMSOL5.5. These designs are hybrid types because different structural changes are combined in a single design for mixing improvement. First of all the straight non-aligned inlets, M-type passive micromixer (SMTM) is analyzed. It is observed that mixing performance is improved because of M-shaped mixing units and non-aligned inlets. This improvement is deemed to be not enough so different shaped obstacles are introduced in the micromixer design. These designs based on obstacles are named horizontal rectangular M-type micromixer, square M-type micromixer, and vertical rectangular M-type micromixer. The mixing index for SMTM, square M-type micromixer, horizontal rectangular M-type micromixer, and vertical rectangular M-type micromixer at Reynolds number Re = 60 is respectively given by 71.1%, 83.21%, 84.45%, and 89.99%. The mixing index of vertical rectangular M-type micromixer was 59.34% − 87.65% for Re = 0.5–100. Vertical rectangular M-type micromixer is concluded with the better-mixing capability design among the proposed ones. Based on these simulation results, the vertical rectangular M-type micromixer design can be utilized for mixing purposes in biomedical applications like nanoparticle synthesis and biomedical sample preparation for drug delivery.